Cost-effectiveness of colorectal cancer screening - Lansdorp_Vogelaar, Iris; Knudsen, A.; Brenner, H. (2011)
Colorectal cancer is an important public health problem. Several screening methods have been shown to be effective in reducing colorectal cancer mortality. The objective of this review was to assess the cost-effectiveness of the different colorectal cancer screening methods and to determine the preferred method from a cost-effectiveness point of view. Five databases (MEDLINE, EMBASE, the Cost-Effectiveness Analysis Registry, the British National Health Service Economic Evaluation Database, and the lists of technology assessments of the Centers for Medicare and Medicaid Services) were searched for cost-effectiveness analyses published in English between January 1993 and December 2009. Fifty-five publications relating to 32 unique cost-effectiveness models were identified. All studies found that colorectal cancer screening was cost-effective or even cost-saving compared with no screening. However, the studies disagreed as to which screening method was most effective or had the best incremental cost-effectiveness ratio for a given willingness to pay per life-year gained. There was agreement among studies that the newly developed screening tests of stool DNA testing, computed tomographic colonography, and capsule endoscopy were not yet cost-effective compared with the established screening options.